2020
DOI: 10.1186/s13673-020-00253-7
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative behavior, performance and engagement with visual analytics tasks using mobile devices

Abstract: Interactive visualizations are external tools that can support users’ exploratory activities. Collaboration can bring benefits to the exploration of visual representations or visualizations. This research investigates the use of co-located collaborative visualizations in mobile devices, how users working with two different modes of interaction and view (Shared or Non-Shared) and how being placed at various position arrangements (Corner-to-Corner, Face-to-Face, and Side-by-Side) affect their knowledge acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
5
2
Order By: Relevance
“…However, based on our results in this study, we found that B-B was the best one. This result also conflicts with the findings in some prior works (e.g., [3,22]). Their results showed that S-S was the best position for supporting better task performance.…”
Section: Position Arrangement(s)contrasting
confidence: 99%
See 2 more Smart Citations
“…However, based on our results in this study, we found that B-B was the best one. This result also conflicts with the findings in some prior works (e.g., [3,22]). Their results showed that S-S was the best position for supporting better task performance.…”
Section: Position Arrangement(s)contrasting
confidence: 99%
“…Users could communicate more efficiently and share their ideas with lower effort (or movement) because of their close proximity to each other, which would enhance task performance. Earlier research has shown that users placed side-by-side achieved the best task performance when collaborating with mobile devices [22]. Therefore, we expected that the same result could apply to large displays.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 52%
See 1 more Smart Citation
“…These results seem to align with findings in [15], where it was claimed that S-S affords the greatest collaboration experience. Another study also stated that S-S is the most favorable and can improve task efficiency [53]. However, it is inconsistent with what Marquardt et al [15] have suggested, in that C-C promotes further communication.…”
Section: Preference On Position Arrangementsmentioning
confidence: 92%
“…In the physical world, spatial relationships and the positioning of people in close proximity can significantly influence their performance and behavior during collaboration [15]. That is, different relative physical orientations afford different types of collaborative styles and user experiences when working together (e.g., competition vs. collaboration) [52,53]. Whether the same applies to VR environments is not clear because there is not much research that has looked at this in detail.…”
Section: Collaborators' Position Arrangementsmentioning
confidence: 99%